Relationship between Officer Knowledge and Resources with Healthy Family Index Achievement in Konawe Islands Regency - Mendri, Ni Ketut; Saafi, La Ode; Tasnim, Tasnim (Waluya The International Science of Health Journal, 2024)
Introduction: Based on the initial data collection, the factors that are obstacles or problems so that the Family Health Index in Konawe Islands Regency has not increased or has not become a healthy status, these factors include knowledge, resources, financing/funding, policies, facilities and infrastructure and so on. For this reason, researchers are interested in conducting research on "The Relationship between Knowledge and Resources of Officers and the Achievement of the Healthy Family Index in Konawe Islands Regency". Method: This type of research is quantitative research with a Cross Sectional Study approach, which was conducted at 8 Health Centers in Konawe Islands Regency. The population was 163 officers and the sample was 100 samples with Simple Random Sampling determination, descriptive and inferential data analysis. Result: The results of the Fisher's Exact Test statistical test at a 95% confidence level (α = 0.05) show that the Fisher's Exact Test p = 0.001 < 0.05 value of X2table = 3.841 and the results of the chi square statistical test of officer resources at a 95% confidence level (α = 0.05) show that the X2count value = 14.710 > X2table value = 3.841, Conclusion: There is a weak relationship between the knowledge and resources of officers with the healthy family index in Konawe Islands Regency, Southeast Sulawesi Province.